Visible-Light-Induced Photodegradation of Methylene Blue Using Mn,N-codoped ZrTiO4 as Photocatalyst - Akhmad Syoufian; Rian Kurniawan (Universitas Gadjah Mada, 2023)
Composites of manganese and nitrogen-codoped zirconium titanate (Mn,N-codoped ZrTiO4) had been synthesized by the sol-gel method as a visible-light responsive photocatalyst for the photodegradation of methylene blue (MB). Synthesis was conducted at 25 °C using titanium(IV) isopropoxide, zirconium oxide, urea, and manganese(II) chloride. Mn,N-codoped ZrTiO4 containing fixed 10% nitrogen dopant (wN/wTi) with various Mn dopant contents (2, 4, 6, 8, and 10% wMn/wTi) and calcination temperatures (500, 700, and 900 °C) had been investigated. All of the Mn,N-codoped ZrTiO4 exhibit a band gap within the visible range (2.51 to 2.74 eV). Photodegradation of MB was performed under visible light illumination for 120 min. The highest activity was achieved up to 7.7 µg L−1 min−1, which was obtained from Mn,N-codoped ZrTiO4 calcined at 500 °C containing 6% Mn and 10% N dopants.